PENGARUH GAJI DAN MOTIVASI TERHADAP KINERJA GURU PADA SMA SWASTA BAGAN SINEMBAH, ROKAN HILIR, RIAU - Sari, Wardani Purnama (Fakultas Ilmu Sosial Universitas Negeri Padang, 2016)
ABSTRACT This research aims to analyze the effect of salary and motivation on performance of teachers. The population of this research is the private HIGH SCHOOL teachers throughout the District of Rokan Hilir Bagan Sinembah totalling 137 persons. Sample in this study consisted of 135 people determined through proportional random sampling. Engineering data collection used by providing questionnaires. The data collected are then analyzed using statistics in the form of Structural Equation Modeling (SEM) with AMOS. The results showed that: 1) salary effect significantly to the motivation of teachers, (2) the salary effect significantly to teaching skills, (2) motivation influence significantly to teaching skills, (3) teaching skills influence significantly to the performance of teachers, (4) salary effect significantly to the performance of teachers, ((6) motivation influence significantly to the performance of teachers, (7) the salary effect significantly to the performance of teachers through teaching skills (8) motivation effect significantly to teacher performance through teaching skills.Keywords: Salary, motivation, teaching skills, job performance